OPTIMIZATION OF MANAGEMENT TACTICS FOR PREGNANT WOMEN AFTER USING ART IN WOMEN WITH ENDOCRINE FACTOR INFERTILITY - Островская, Ольга Васильевна; Баринов, Сергей Владимирович; Шамина, Инна Васильевна; Тирская, Юлия Игоревна; Турчанинов, Денис Владимирович (Mother and Baby in Kuzbass, 2022)
One of the main problems of modern obstetrics in pregnant women, including after ART, is the development of effective measures for the prevention of maternal and perinatal morbidity and mortality. To date, there is a sufficient number of regulatory documents that allow prolonging pregnancy, however, the algorithms for managing pregnant women after ART are not perfect enough, there are a number of unresolved issues, and therefore a combined approach to pregnancy management is of interest after ART.The aim of the study is to optimize the management of pregnant women and improve the outcome of childbirth in pregnant women after ART with endocrine factor infertility.Materials and methods. We examined 149 pregnant women with endocrine factor infertility after ART with singleton pregnancies, which were divided into 3 groups. The main group (I) consisted of 60 women with an integrated approach to pregnancy management (all pregnant women received micronized progesterone in combination with the Dr. Arabin obstetric pessary). Comparison group II (n = 49) consisted of pregnant women using only micronized progesterone. Control group III (n = 40) included pregnant women with a retrospective analysis of the course of pregnancy.Research results. Analysis of the course of pregnancy revealed significant differences in the frequency of the threat of termination of pregnancy: in the main group 69.9 % (42/60), in the comparison group – 44.8 % (22/49) (p = 0.002). The most frequent complication of pregnancy in the main group was the development of moderate and severe preeclampsia – 15.0 % (9/60), as a result of the consequences of placenta formation at low PIGF – 16.4 pg/ml. Differences in the frequency of RPD were revealed: in the main group – 3.3 %, in the comparison group – 16.3 % (p < 0.05, χ2 = 4.017), which is 4.9 times higher. In the control group – 17.5 %, which is 5.3 times higher than the main group (p < 0.05, χ2 = 2.995).The average value of the anterior cervical uterine angle in women with PR was 98.4° (87-104°) in the main group (15/60) and 97.5° (85-105°) in comparison group II (15/49). The interval of the value of the anterior ma-to-cervical angle threatened by the development of PR can be taken as 98.0° (85-105°).Conclusion. An integrated approach allows to reduce the frequency of early PR by 4.9 times in comparison with the comparison group (p < 0.05, χ2 = 4.017), and 5.3 times in comparison with the control group (p < 0.05, χ2 = 2.995), and to receive full-term babies 1.8 times more often in comparison with the control group (p < 0.001).
Keywords: pregnancy after ART; endocrine infertility; obstetric pessary; premature birth; PIGF; uterocervical angle